Transparency Problems in Cash Flow Transformation and Reserves Management in Islamic Investment Accounts - Badreldin, Ahmed (Journal of Islamic Finance, 2019)
Islamic banks must comply with the interest rate prohibition to maintain Shari’ah compliance. This means that depositors cannot be offered fixed guaranteed returns on their investments. As an alternative, Islamic banks offer profit sharing investment accounts that depend on underlying investments to generate their cash flows. These cash flows are then transformed by the management before they are finally paid out to the investment account holders. The objective of these cash flow transformations is to transform the stochastic returns of the underlying investment to more stable (to an extent non-stochastic) returns for investment account holders. This is required or recommended by regulatory authorities and aims to mitigate system-wide mass withdrawals by investors (Withdrawal Risk). However, managing such reserves comes at a price, and this is the focus of this paper. These reserves create a veil of intransparent practices while hiding the actual performance of the investment accounts. Furthermore, they may end up defrauding some depositors from their deserved profits (inter-generational reserves ownership problem). Finally, mitigating withdrawal risk by matching the returns of competing riskless deposits while ignores the risks of Islamic investment accounts that associated with investing in the real economy. Some of these issues have gone relatively unnoticed in the literature or at least not combined in a structured manner. Therefore, it is highlighted in this paper the problematic nature from an ethical and Shari’ah compliance perspective and if not from a pure financial regulatory one.